Penerapan PSAK NO. 102 Atas Transaksi Murabahah: Studi Pada Baitul Maal Wa Tamwil Di Depok, Jawa Barat - Febrian, Rani; Mardian, Sepky (IKONOMIKA, 2017)
This study aims to determine the accounting treatment of murabahah (recognition, measurement, presentation and disclosure) in accordance with PSAK no. 102. BMT in Depok was studied. The descriptive analysis with qualitative and quantitative approaches was used to deploy the questionnaires to respondents. The study showed that the accounting treatment of murabahah in BMT Depok is not all adopted PSAK no. 102 properly. The average value of the percentage only reached 68.4%. There are weaknesses in the educational background of the respondents were limited to the knowledge of transaction records BMT.